2009
DOI: 10.1128/jvi.02601-08
|View full text |Cite
|
Sign up to set email alerts
|

Entry of Herpes Simplex Virus 1 and Other Alphaherpesviruses via the Paired Immunoglobulin-Like Type 2 Receptor α

Abstract: Herpes simplex virus 1 (HSV-1) enters cells either via fusion of the virion envelope and host cell plasma membrane or via endocytosis, depending on the cell type. In the study reported here, we investigated a viral entry pathway dependent on the paired immunoglobulin-like type 2 receptor ␣ (PILR␣), a recently identified entry coreceptor for HSV-1 that associates with viral envelope glycoprotein B (gB). Experiments using inhibitors of endocytic pathways and ultrastructural analyses of Chinese hamster ovary (CHO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
60
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 81 publications
(63 citation statements)
references
References 49 publications
3
60
0
Order By: Relevance
“…In addition, different host receptors in the same cell type can direct HSV to different pathways (8). Studies in various cell backgrounds have indicated that cellular receptors such as nectin-1, nectin-2, paired immunoglobulin-like type 2 receptor alpha (PILR␣), and integrins can influence the entry route (3,(8)(9)(10)(11)(12)(13). This study tests the hypothesis that one or more envelope proteins direct HSV to an endocytic entry route.…”
mentioning
confidence: 81%
“…In addition, different host receptors in the same cell type can direct HSV to different pathways (8). Studies in various cell backgrounds have indicated that cellular receptors such as nectin-1, nectin-2, paired immunoglobulin-like type 2 receptor alpha (PILR␣), and integrins can influence the entry route (3,(8)(9)(10)(11)(12)(13). This study tests the hypothesis that one or more envelope proteins direct HSV to an endocytic entry route.…”
mentioning
confidence: 81%
“…Recently, it has been suggested that gBspecific receptors, such as PILR␣, or other cellular plasma membrane factors determine whether virions enter predominantly via fusion at the plasma membrane or via receptor-mediated endocytosis (pH dependent or pH independent), followed by fusion of the viral envelope with endosomal membranes (15).…”
mentioning
confidence: 99%
“…It was recently shown that HSV-1 gB and PRV gB engage the paired immunoglobulin-like type 2 receptor ␣ (PILR␣) and that the process is required for viral entry into cells transduced with this receptor (1,40). PILRs are expressed in a variety of tissues, including the nervous system (40).…”
mentioning
confidence: 99%